Return Migration and the "Healthy Immigrant Effect" - Monika Sander (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
According to the "healthy immigrant effect" (HIE), immigrants upon arrival are healthier than locally born residents. However, this health advantage is supposed to diminish or even disappear over a relatively short period and the immigrants' health status is converging to that of the natives. The causes for this gradient of immigrants' health are subject to an ongoing discussion and the underlying trajectories are not yet fully understood. This paper investigates whether return migration can serve as an additional explanation for the declining health of immigrants, and thus aims at shedding some light on the trajectories underlying the HIE. The data used are drawn from 13 waves of the German Socio-Economic Panel. Using a random-effects probit model, this analysis explores the factors influencing re-migration by means of a sample of 4,426 migrants. In line with the existing literature, the study shows that e.g. having spouse and children in the home country, or being non-working or jobless yield a higher return probability, whereas all factors associated with attachment to Germany (e.g. language fluency, German citizenship, house ownership) reduce the probability of re-migration. Additionally, the results indicate that men reporting poorer health ('good', 'satisfactory', 'poor' or 'bad') are significantly less likely to return home relative to male immigrants who describe their health as 'very good'. However, for women, the effects are adverse to that of men, and none of the health coefficients for women is significant. Hence - at least for men - re-migration can be seen as an additional explanation for the HIE.
Keywords: C25; F22; I19; 330; Return migration; healthy immigrant effect; SOEP